2021
DOI: 10.1108/tr-02-2021-0088
|View full text |Cite
|
Sign up to set email alerts
|

Chineseness and behavioural complexity: rethinking Chinese tourist gaze studies

Abstract: Purpose This study aims to reconsider Chinese tourist gaze studies, examining the extent to which extant studies and theoretical models relating to the Chinese tourist gaze have overcome the Eurocentric limits of John Urry’s concept of the tourist gaze and elaborated the complexity of Chinese tourists’ gazes and visual practices. Design/methodology/approach Content analysis is carried out, examining research articles, books, book chapters and PhD and MSc theses collected from multiple English and Chinese data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…It is likely that in-depth qualitative approaches can be valuable in this regard. While this study points to an East-West divide in terms of IAS perceptions and attitudes among visitor groups, to address any possibility of falling into a culturally essentialist interpretation of these findings (Li et al 2021), further in-depth qualitative research will be valuable in ascertaining why such attitudes prevail.…”
Section: Visitors' "Ias Orientation"mentioning
confidence: 93%
See 2 more Smart Citations
“…It is likely that in-depth qualitative approaches can be valuable in this regard. While this study points to an East-West divide in terms of IAS perceptions and attitudes among visitor groups, to address any possibility of falling into a culturally essentialist interpretation of these findings (Li et al 2021), further in-depth qualitative research will be valuable in ascertaining why such attitudes prevail.…”
Section: Visitors' "Ias Orientation"mentioning
confidence: 93%
“…Of course, to consider that all Chinese (or all Asians) subscribe to a consistent human-nature cosmology runs the risk of essentializing Chinese-ness and/or Asian-ness (Li et al 2021),…”
Section: Ethnicity and Attitudes Toward Nature And Iasmentioning
confidence: 99%
See 1 more Smart Citation
“…The Concept of Tourist Gaze Tourist gaze describes how people view the places they visit, emphasizing visual consumption in tourists' experiences (Urry, 1990(Urry, , 1995. It critically shifts the focus of tourism research from institutional production to tourist consumption (Li et al, 2021). From the perspectives of cognition and consciousness, the eye gaze signals the direction of one's attention and future actions (Land & Hayhoe, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Urry and Larsen (2011) suggested that vision can orient the functions of other sensations, and the tourist gaze constitutes a holistic way of viewing the world rather than a singular sense. Recently, scholarly endeavors also explore the tourist gaze across various contexts and interpret it as a more heuristic concept that encompasses both objective and subjective nature, reflects dynamic human interactions, and serves as a vehicle to achieve an experience (e.g., Li, 2015;Urry & Larsen, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%